Minority Protection in Voting Mechanisms – Experimental Evidence - Dirk Engelmann; Hans Peter Grüner; Timo Hoffmann; Alex Possajenikov (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Under simple majority voting an absolute majority of voters may choose policies that are harmful to minorities. It is the purpose of sub- and super-majority rules to protect legitimate minority interests. We study how voting rules are chosen under the veil of ignorance and whether there are systematic biases in these choices. In our experiment, individuals choose voting rules for given distributions of gains and losses that can arise from a policy, but before learning their own valuation of the policy. We find that subjects on average adjust the voting rule in line with the skewness of the distribution. As a result, a higher share of the achievable surplus can be extracted with the suggested rules than with exogenously given simple majority voting. While the rule choices are not significantly biased towards under- or overprotection of the minority, towards majority voting or towards status-quo preserving rules, they only imperfectly reflect the distributions of benefits and costs. In expectation this leads to only 63% of the surplus being extracted. The participants are heterogeneous with respect to how well their rule choices adapt to the distribution of valuations, with a large share of the surplus loss caused by a small group of participants.
Keywords: D72; C91; 330; minority protection; voting; experiments